Novel NASICON-type high-voltage sodium vanadium phosphate material for NA ion battery
By using the material AxV(2-y-z)MyM'z(PO4)3 with formula (I), the weight loss, limited capacity and low work of the traditional Na3V2(PO4)3 positive electrode material is solved by using the solid solution single-phase reaction mechanism. The voltage problem achieves higher energy density and small volume expansion/shrinkage effects.
Patent Information
- Application Number
- CN202380036916.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-29
- Filing Date
- 2023-04-27
- Publication Date
- 2025-02-18
AI Technical Summary
The existing Na3V2 (PO4)3 positive electrode materials have weight loss and limited capacity in electrochemical reactions, and have low operating voltage, making it difficult to meet the needs of high energy density and small volume expansion/contraction.
AxV(2-y-z)MyM'z(PO4)3 with formula (I), where A is Na or Li, M is an electroactive transition element, and M' is an electroactive element, through a solid solution single-phase reaction mechanism Improve operating voltage and energy density.
A higher theoretical weight energy density (about 464Wh/kg) than traditional Na3V2(PO4)3 materials and smaller volume changes, and the operating voltage is ramped up in the range of 3.0V to 4.3V, improving the ability of the material Continuity and cost-effectiveness.
Smart Images

Figure CN119486965A_ABST
Abstract
Description
[0001] The present invention relates to a novel Na-based positive electrode active material for a Na-ion battery. The present invention also relates to a method for preparing the material and its use as an electrode material. The present invention also relates to an electrode material comprising the Na-based material and to a battery comprising the electrode. Background Art
[0002] Lithium-ion batteries have been widely used in electric vehicles and portable devices due to their satisfactory energy and power density. However, lithium resources are expensive and unevenly distributed around the world, making it challenging to meet the urgent demand for large-scale energy storage systems.
[0003] The most attractive alternative to lithium-ion batteries in terms of chemical element abundance and cost is sodium, due to the abundant and evenly distributed resources and relatively low material cost compared to lithium-ion batteries.
[0004] The performance of Na-ion batteries is partly related to the capacity of the cathode material. Sodium layered transition metal oxides, Prussian blue analogs, and polyanionic compounds are considered as possible cathode materials for Na-ion batteries. Polyanionic compounds with NASICON structure are potential choices as cathode materials because of their structural stability, rate performance, and long cycle life. Among them, Na3V2(PO4)3 has been widely studied and provides a theoretical capacity of 117.6 mAh / g. 4+ / V 3+ Redox couple. During the electrochemical charge and discharge process, the two Na + Ions can be reversibly exchanged via a two-phase mechanism between Na3V2(PO4)3 and Na1V2(PO4)3 at about 3.4 V vs. Na + Na3V2(PO4)3 undergoes a moderate volume change of about 8.2% during the electrochemical reaction.
[0005] However, due to the last Na + The large migration energy does not occur in the electrochemical reaction. + The extraction of (from Na1V2(PO4)3 to V2(PO4)3) results in weight loss and limited capacity. More importantly, the working voltage of Na3V2(PO4)3 is 3.4V relative to Na + / Na, which is relatively low.
[0006] Therefore, there remains a need for new cathode materials that exhibit improved performance compared to prior art cathode materials. Purpose of the invention
[0007] One of the objects of the present invention is to provide an electrode material, preferably a positive electrode material, which exhibits better performance than the electrode materials of the prior art, in particular better performance than conventional Na3V2(PO4)3 or Li3V2(PO4)3 materials.
[0008] Specifically, an object of the present invention is to provide an electrode material, preferably a positive electrode material, which exhibits a relative + / Na or Li + / Li's high operating voltage.
[0009] Another specific object of the present invention is to provide an electrode material, preferably a positive electrode material, which provides a higher energy density than conventional Na3V2(PO4)3 or Li3V2(PO4)3 materials.
[0010] Another specific object of the present invention is to provide an electrode material, preferably a positive electrode material, which has smaller volume expansion / contraction during electrochemical operation than conventional Na3V2(PO4)3 or Li3V2(PO4)3 materials.
[0011] Another object of the present invention is to provide an electrode material that shows a single-phase reaction mechanism during the charging and discharging process. DETAILED DESCRIPTION
[0012] The present invention relates to a material having formula (I): A x V (2-y-z) M y M' z (PO4)3(I) in: A is Na or Li or a mixture of Na and Li, 1 <x<3, 0≤y<1, 0≤z<1 M is an electroactive transition element or a mixture of at least two electroactive transition elements, M' is an electro-inactive element or a mixture of at least two electro-inactive elements, and The material having formula (I) presents to Varying V / Z ratio (volume of crystal unit cell per formula unit).
[0013] Transition elements refer to transition metals.
[0014] The inventors have found that the material of formula (I) according to the present invention has many interesting physical and electrochemical properties compared to the existing positive electrode materials Na3V2(PO4)3 or Li3V2(PO4). For example, in the case where A=Na, the material of formula (I) shows a high conductivity at 2.5-4.3V relative to Na + About two reversible Na / Na exchanges within the voltage window + ions, and higher than the corresponding theoretical capacity of Na3V2(PO4)3. In addition, the average operating voltage of the material according to the present invention has been increased to about 3.75V relative to Na + / Na (about 3.4V from regular Na3V2(PO4)3). In addition, the electrochemical reaction mechanism when sodium is extracted from / intercalated into this material occurs via a solid solution (single phase) mechanism, with Na + The operating voltage increases continuously as it is electrochemically extracted, which is different from the two-phase mechanism encountered with the "classic" Na3V2(PO4)3. This is very impressive because it allows for more cost-effective monitoring of the state of charge than systems with a flat voltage curve. Finally, instead of the "classic" constant voltage 3.4V process for Na3V2(PO4)3, the operating voltage of the material of the present invention increases in a ramp-up manner from 3.0V to 4.3V relative to Na + Due to the subsequent increase in operating voltage, the theoretical gravimetric energy density of the material of the present invention is subsequently increased by about 15% to 464Wh / kg when compared to conventional Na3V2(PO4)3.
[0015] Preferably, the electroactive transition element M is selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Nb and Mo, more preferably selected from the group consisting of Ti, V, Cr, Mn, Fe and Nb.
[0016] Preferably, the inactive element M' is selected from the group consisting of Mg, Al, Sc, Y, Zr, Er and Ta, more preferably from the group consisting of Mg, Al and Zr.
[0017] For light doping, the electrically inactive element M' is used, especially if it is in the +2 (Mg 2+ ) or +3(Al 3+ ) oxidation state, when two Na + This allows V to be obtained at high voltages. 4+ / V 5+ Redox couple. It thus allows to increase both the energy density offered and the sustainability of the material.
[0018] When M is a mixture of at least two electroactive transition elements, y represents the sum of the mole fractions of each transition element contained in M.
[0019] When M' is a mixture of at least two inactive elements, z represents the sum of the mole fractions of each inactive element contained in M'.
[0020] Preferably, 0≤y≤0.8, more preferably 0≤y≤0.5, even more preferably 0≤y≤0.2.
[0021] Preferably, 0≤z≤0.5, more preferably 0≤z≤0.2.
[0022] According to an embodiment, y=0 and / or z=0.
[0023] Preferably, x ranges from 1.1 to 2.9, preferably from 1.2 to 2.8, preferably from 1.3 to 2.7, preferably from 1.4 to 2.6, preferably from 1.5 to 2.5, preferably from 1.6 to 2.4, preferably from 1.7 to 2.3, preferably from 1.8 to 2.2, preferably from 1.9 to 2.1, and / or any other suitable combination.
[0024] Typically, x, y and z are selected so as to ensure electroneutrality of the material having formula (I).
[0025] According to the present invention, the V / Z ratio of a material having formula (I) is the unit cell volume (in units of formula) This feature is well known to the skilled person. The V / Z ratio is determined by fitting a powder diffraction curve, for example an X-ray or neutron diffraction pattern of a powder of the material having formula (I) according to the invention, using the so-called LeBail method. The X-ray or neutron diffraction pattern is usually obtained at 25° C. (298 K) (unless otherwise mentioned). The V / Z ratio is independent of the space group used to represent the crystal structure of the material having formula (I).
[0026] Advantageously, the material of formula (I) is a single phase material.
[0027] Single-phase materials are solid materials consisting of a distinct solid phase described by a crystal structure giving the corresponding atomic positions in a so-called unit cell described by an appropriate space group.
[0028] According to one embodiment, A=Li.
[0029] In this embodiment, the material having formula (I) preferably exhibits to Varying V / Z ratio.
[0030] According to another embodiment, A is a mixture of Li and Na. According to this embodiment, x represents the sum of the mole fraction x' of the Li element and the mole fraction (1-x') of the Na element.
[0031] Preferably, 0≤x′≤1.
[0032] In this embodiment, the material having formula (I) preferably exhibits to Varying V / Z ratio.
[0033] According to another embodiment, A=Na.
[0034] In this embodiment, the material having formula (I) preferably exhibits to Preferably from to Varying V / Z ratio.
[0035] Preferably, the V / Z ratio is from to Preferably from to Preferably from to Preferably from to Preferably from to Preferably from to and / or any other suitable combination of range variations.
[0036] Preferably, when 1.8≤x≤2.3, the V / Z ratio is to Preferably from to change.
[0037] More preferably, when x=2, the V / Z ratio changes from to Advantageously from to This means that the V / Z ratio is preferably further defined with the condition that if x=2, the V / Z ratio changes from to Advantageously from to change.
[0038] The material of formula (I) according to the present invention can be structurally described using a hexagonal unit cell or alternatively a monoclinic or triclinic unit cell, depending on the overall Na content and possible Na ion ordering that produces slight distortions in the framework. Preferably, the material of formula (I) is described using a hexagonal unit cell, which is more symmetrical than a monoclinic or triclinic description.
[0039] Preferably, the material having formula (I) has a crystal lattice in which the overall symmetry is described in terms of the R32, R-3, R-3c, C2 / c, P-1 or P-3 space groups.
[0040] More preferably, the material having formula (I) is structurally described by a hexagonal unit cell and an R-3c space group.
[0041] Preferably, the material of formula (I) wherein A=Na has the following lattice parameters when described by a hexagonal unit cell: a 六方 At 8.60 and between 8.64 and between, more preferably substantially equal to and c 六方 At 21.80 and between 21.88 and between, more preferably substantially equal to
[0042] Preferably, the c / a ratio ranges from 2.500 to 2.550, more preferably from 2.505 to 2.545, more preferably from 2.510 to 2.545, more preferably from 2.515 to 2.540, more preferably from 2.520 to 2.538, more preferably from 2.525 to 2.536, more preferably from 2.530 to 2.535, more preferably from 2.531 to 2.535 and / or any other suitable combination.
[0043] Preferably, in the material of formula (I) wherein A=Na, when 1.8≤x≤2.3, the c / a ratio varies from 2.520 to 2.545 when described by a hexagonal unit cell. Preferably, in the material of formula (I), when x=2, the c / a ratio varies from 2.520 to 2.540 when described by a hexagonal unit cell.
[0044] Materials of formula (I) where A = Na can be described using a rhombohedral (R-3c) structure, where the sodium ions are located at two sodium sites, Na(1) and Na(2). Site Na(1) is 6-coordinated and has a 3D structure along the c 六方Sandwiched between two VO6 octahedra. The Na(2) site is 8-coordinated and occupies the interstitial space formed by the M2(PO4)3 units.
[0045] Preferably, the material of formula (I) is described as a rhombohedral (R-3c) crystal structure having two sodium sites, Na(1) and Na(2), the average filling rate of the Na(1) site being from 0 to 1, and the average filling rate of the Na(2) site being from 0 to 1. Filling rate means the occupancy of the Na(1) and Na(2) sites on the unit cell. Filling rate means the ratio of the number of occupied sites to the number of available sites. It should be noted that the multiplicity of the Na(2) site is equal to three times the multiplicity of the Na(1) site and therefore the maximum sodium per formula (I) is equal to 1 at the Na(1) position and equal to 3 at the Na(2) position.
[0046] Preferably, the average filling fraction of Na(1) sites varies from 0.2 to 0.95, preferably from 0.3 to 0.9, more preferably from 0.5 to 0.8, even more preferably from 0.6 to 0.7, advantageously being substantially equal to 0.66.
[0047] Preferably, the average filling fraction of the Na(2) sites varies from 0 to 0.9, preferably from 0.4 to 0.9, more preferably from 0.45 to 0.7, even more preferably from 0.5 to 0.6, advantageously being substantially equal to 0.54.
[0048] The present invention also relates to a method for preparing a material having formula (I), comprising the following steps: a) Mixed A3V (2-α) Z α (PO4)3 and A1V (2-β) Z' β (PO4)3, preferably under an inert atmosphere, to obtain an initial mixture, in A is Li or Na or a mixture of Na and Li, Z and Z' are elements independently selected from electroactive transition elements, electroactive non-electroactive elements and mixtures thereof, 0≤α<1 and 0≤β<1, b) heating the initial mixture at a temperature between 300° C. and 700° C., preferably under an inert atmosphere or under vacuum.
[0049] Preferably, in the initial mixture, Na3V (2-w) M' w The mole fraction of (PO4)3 is p and Na1V (2-z) M” zThe mole fraction of (PO4)3 is (1 - p), where 0 < p < 1. More preferably, p varies from 0.05 to 0.95, preferably from 0.1 to 0.9, preferably from 0.15 to 0.85, preferably from 0.2 to 0.8, preferably from 0.25 to 0.75, preferably from 0.3 to 0.7, preferably from 0.35 to 0.65, preferably from 0.4 to 0.6, preferably from 0.45 to 0.55, and / or any other suitable combination range.
[0050] This method is a solid solution method. In the initial mixture, A3V (2-α) Z α (PO4)3 and A1V (2-β) Z’ β The mole fraction of (PO4)3 determines the product A x V (2-y-z) M y M’ z (PO4)3 has an x value, where the relationship is x = 1 + 2p.
[0051] Preferably, the electroactive transition element is Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Nb or Mo, more preferably Ti, V, Cr, Mn, Fe or Nb.
[0052] Preferably, the non - electroactive element is Mg, Al, Sc, Y, Zr, Er or Ta, more preferably Mg, Al or Zr.
[0053] Preferably, the method includes granulating the initial mixture in step a) (preferably in an inert atmosphere) to obtain step a’) between step a) and b).
[0054] The use of the granule creates better contact between A3V (2-α) Z α (PO4)3 and A1V (2-β) Z’ β (PO4)3 particles and is thus beneficial to the efficiency of step b).
[0055] Preferably, during step b), the initial mixture (or granule) is heated at a temperature between 400 °C and 600 °C, more preferably between 500 °C and 550 °C.
[0056] Preferably, the method further includes preferably preparing A1V (2-α) Z α (PO4)3 by chemical oxidation of A3V (2-β) Z’ β (PO4)3 as an initial step before step a).
[0057] Preferably, the process further comprises a step c) of cooling the heated initial mixture (or pellets) obtained at the end of step b) to a temperature comprised between 20 and 40°C.
[0058] According to the present invention, the inert atmosphere may be an atmosphere comprising N2 and / or Ar and less than 2 ppm of O2 and / or less than 2 ppm of H2O.
[0059] According to another embodiment, Z and Z' are identical.
[0060] According to another preferred embodiment, Z is an electroactive transition element or a mixture of at least two electroactive transition elements, and Z' is an electroactive element or a mixture of at least two electroactive elements, or Z is an inactive element or a mixture of at least two inactive elements, and Z' is an active transition element or a mixture of at least two active transition elements. In other words, either Z corresponds to M and Z' corresponds to M', or Z corresponds to M' and Z' corresponds to M of the material of formula (I).
[0061] Preferably, α=0 and / or β=0.
[0062] The present invention also relates to a method for preparing a material having formula (I), comprising the following steps: 1) A3V (2-y-z) M y M' z (PO4)3 is dispersed in a solvent, preferably an organic solvent, in A is Na or Li or a mixture of Na and Li, 0≤y<1, 0≤z<1, M is an electroactive transition element or a mixture of at least two electroactive transition elements, M' is an electro-inactive element or a mixture of at least two electro-inactive elements, 2) Add oxidant to A3V (2-y-z) M y M' z In the dispersion of (PO4)3, 3) stirring the resulting mixture, and 4) Get an A x V (2-y-z) M y M' z (PO4)3, of which 1 <x<3。
[0063] M, M', y and z are as defined above for the material of formula (I) according to the invention.
[0064] Preferably, y = 0 and / or z = 0.
[0065] The molar ratio between the amount of the oxidizing agent and A3V (2-y-z) M y M' z (PO4)3 is n. Preferably, 0 < n < 2. More preferably, n varies from 0.1 to 1.9, preferably from 0.2 to 1.8, preferably from 0.3 to 1.7, preferably from 0.4 to 1.6, preferably from 0.5 to 1.5, preferably from 0.6 to 1.4, preferably from 0.7 to 1.3, preferably from 0.8 to 1.2, preferably from 0.9 to 1.1, and / or any other suitable combination range.
[0066] Added to A3V (2-y-z) M y M' z The amount of the oxidizing agent in the dispersion of M' x V (2-y-z) M y M' z (PO4)3 determines the value of x in A3V
[0067] Preferably, the oxidizing agent is added dropwise to A3V (2-y-z) M y M' z (PO4)3 dispersion.
[0068] Preferably, the oxidizing agent is selected from the group consisting of NO2BF4, Na2S2O8, I2 and CHCl3. Advantageously, the oxidizing agent is NO2BF4.
[0069] The present invention also relates to the use of the material of formula (I) according to the invention as an electrode active material for a battery, preferably as a positive electrode active material for a Li-ion or Na-ion battery, more preferably a Na-ion battery.
[0070] The material of formula (I) can be used together with one or more other compounds conventionally used (such as binders and / or conductive additives).
[0071] The one or more conductive additives can be selected from carbon fibers, carbon black, carbon nanotubes, graphite and the like.
[0072] One or more binders can advantageously be selected from fluorinated binders, in particular from polytetrafluoroethylene and polyvinylidene fluoride, carboxymethyl cellulose-derived polymers, polysaccharides and latexes, in particular latexes of the styrene-butadiene rubber type.
[0073] The present invention further relates to an electrode for a battery, preferably for a Li-ion or Na-ion battery, more preferably for a Na-ion battery, comprising at least one material according to the invention having formula (I).
[0074] The electrode according to the invention can be the positive electrode of a lithium generator or a sodium generator.
[0075] Advantageously, the electrode according to the invention is a positive electrode for a secondary sodium or sodium-ion battery.
[0076] The electrodes can be deposited on a conductive current collector. This current collector can be aluminum.
[0077] Preferably, the material of formula (I) represents from 10 to 95% by weight of the total weight of the electrode, in particular greater than 40% by weight and more particularly from 80 to 95% by weight relative to the total weight of said electrode.
[0078] The present invention further relates to a battery, preferably a Li-ion or Na-ion battery, more preferably a Na-ion battery, comprising at least one material of the formula (I) according to the present invention as an electrode active material, preferably as a positive electrode active material.
[0079] The secondary sodium battery according to the invention may more particularly comprise a positive electrode according to the invention and a negative electrode, for example, consisting of disordered carbon. In contrast to the secondary lithium battery, sodium ions, unlike lithium ions, do not react with aluminum to form an alloy, and it can be deposited on an aluminum current collector.
[0080] The negative electrode material may more specifically be a material having a low specific surface area (<10 m 2 / g) of disordered carbon, the particle size of which is from about one micron to about ten microns. It can be selected from hard carbon (non-graphitizable carbon) or soft carbon (graphitizable carbon).
[0081] In the text, unless otherwise stated, the expressions “between… and…” and “ranging from… to…” and “varying from… to…” are equivalent and are intended to mean that the limit values are included. BRIEF DESCRIPTION OF THE DRAWINGS
[0082] Figure 1 Represents the in situ synchrotron X-ray powder diffraction pattern recorded every 3°C when a Na3V2(PO4)3 / Na1V2(PO4)3 mixture (1:1 molar ratio) was heated to 500°C and then cooled to 35°C.
[0083] Figure 2A series of XRD patterns of several Na3V2(PO4)3 and Na1V2(PO4)3 mixtures before heat treatment measured at 25°C (left) and Na1V2(PO4)3 after heat treatment up to 500°C-550°C measured at 25°C. x A series of XRD patterns of V2(PO4)3 single phase (right).
[0084] Figure 3 is the Na2V2(PO4)3 refined by full pattern matching as x changes with conventional Na3V2(PO4)3 and Na1V2(PO4)3 as well as electrochemically observed Na2V2(PO4)3 x Plots of the evolution of the V / Z (right) and c / a (left) ratios of the V2(PO4)3 phase.
[0085] Figure 4 XRD patterns of a material according to the invention having formula (I) where x=2 (top) and electrochemical observations of Na2V2(PO4)3 collected with an in situ cell during cycling (bottom).
[0086] Figure 5 Schematic diagram of the crystal structure of the material having formula (I) according to the present invention wherein x=2 (left) and electrochemically observed Na2V2(PO4)3 (right).
[0087] Figure 6 is Na where x = 2 x Voltage (V vs. Na) of V2(PO4)3 (according to the invention) / Na metal half-cells in the first two cycles as a function of specific capacity (mAh / g) + / Na) (left) and a graph of the specific discharge capacity as a function of cycle number (right).
[0088] Figure 7 is the operational XRD diagram of Na2V2(PO4)3 as the positive electrode material in a half-cell according to the present invention relative to Na metal during charge and discharge, wherein at 0.1C (≈1 Na in 10h) + ) at C-rates of (a) 2.5-4.4 V and (b) 1.3-3.0 V vs. Na + / Na.
[0089] Figure 8 is the variation of (a) the unit cell volume (V / Z) per chemical formula unit, (b) the c / a ratio, and (c) the Na per chemical formula unit with the number of scans. + The total number of, and (d) the evolution of the Na occupancy factors for Na1 and Na2 sites.
[0090] Fig. 9is a representation of operational XRD measurements of conventional Na3V2(PO4)3 as the cathode material in a half-cell relative to Na metal during charge and discharge, where at 0.1C (≈ 1 Na in 10 h) + ) at a C-rate of (a) 2.5-4.3 V relative to Na + / Na.
[0091] The present invention is illustrated in more detail in the following examples, but it is not limited to these examples.
[0092] Example
[0093] Example 1: Preparation of materials having formula (I)
[0094] 1.1. The material having formula (I) can be prepared from a mixture of Na3V2(PO4)3 and Na1V2(PO4)3.
[0095] Synthesis of Na3V2(PO4)3
[0096] The synthesis of Na3V2(PO4)3 can be carried out in two steps. First, carbon-coated VPO4 is synthesized by mixing stoichiometric amounts of V2O5 (AlfaAesar, 99.6%), H3PO4 (AlfaAesar, 85% in water) and agar (Fisher BioReagents) in deionized water. The solution was stirred overnight at 80°C in an oil bath and then dried overnight at 250°C in an oven. The obtained dry powder was ground and placed in a furnace at 890°C in an Ar atmosphere with a heating ramp of 5°C / min for 2h. Then, Na3PO4 (Acros organics, 96%) was mixed with the resulting VPO4 in a molar ratio of 1:2, and then heated for 2h at 800°C in an Ar atmosphere with a heating ramp of 5°C / min.
[0097] Synthesis of Na1V2(PO4)3
[0098] To prepare Na1V2(PO4)3, chemical oxidation of Na3V2(PO4)3 was performed. Na3V2(PO4)3 was dispersed in acetonitrile (Sigma-Aldrich, 99.8%) using a magnetic stirrer, and the oxidant nitronium tetrafluoroborate (NO2BF4, Sigma-Aldrich, 95%) was introduced dropwise into the dispersed Na3V2(PO4)3 in a 0.1M solution in acetonitrile to perform the following reaction.
[0099] Na3V2(PO4)3+2NO2BF4→Na1V2(PO4)3+2NaBF4+2NO2↑
[0100] The resulting solution was stirred overnight and then filtered and washed with acetonitrile.
[0101] Na x Synthesis of V2(PO4)3
[0102] Na x V2(PO4)3 can be obtained by the following chemical reaction:
[0103] pNa3V2(PO4)3+(1-p)Na1V2(PO4)3→Na 1+2p V2(PO4)3
[0104] The Na3V2(PO4)3 and Na1V2(PO4)3 powders in the desired molar ratio are mixed thoroughly in an Ar-filled glove box and preferably granulated. The resulting powder is then sealed with a gold tube and then heat treated at 500°C for 12 h.
[0105] 1.2. The material having formula (I) according to the present invention can also be prepared by controlling the oxidant during the chemical oxidation process of Na3V2(PO4)3 instead of mixing the two materials (Na1V2(PO4)3 and Na3V2(PO4)3) in different ratios.
[0106] Na3V2(PO4)3 was dispersed in acetonitrile (Sigma-Aldrich, 99.8%) using a magnetic stirrer, and the required amount of 0.1 M solution of nitronium tetrafluoroborate (NO2BF4, Sigma-Aldrich, 95%) in acetonitrile was dropwise introduced into the dispersed Na3V2(PO4)3 to carry out the following reaction.
[0107] Na3V2(PO4)3+xNO2BF4(0 <x<2)→Na 3-x V2(PO4)3+xNaBF4+xNO2↑
[0108] The resulting solution was stirred overnight and then filtered and washed with acetonitrile.
[0109] The same considerations apply to x V 2-y-z M y M' z (PO4)3 materials that can intercalate or release Na according to a two-phase process at an operating voltage that depends on the nature of the redox couple associated with the reduction or oxidation of V and / or M + (Ref. 1-6). For example, it is well known that Na1Ti2(PO4)3 and Na3Ti2(PO4)3 exist (y=2) and can be converted to the other by chemical oxidation or reduction of one of them or by electrochemical Na+ The same is true for Na3AlV(PO4)3 and Na1AlV(PO4)3 (y=0, z=1), NbTi(PO4)3 and Na2NbTi(PO4)3 (y=2), Na3FeV(PO4)3 and Na1FeV(PO4)3 (y=1). These end members can be separated and mixed and heated to produce new Na x V 2-y-z M y M' z (PO4)3 single phase material.
[0110] (1) Masquelier, C.; Croguennec, L. Polyanionic (phosphates, silicates, sulphates, ..) frameworks as electrode materials for rechargeable Li (or Na) batteries, Chem. Rev., 113(8), 6552-6591 (2013)
[0111] (2) F. Lalère, V. Seznec, M. Courty, J. N. Chord & C. Masquelier, Improving the energy density of Na3V2(PO4)3–type positive electrodes through V / Al substitution, J. Mater. Chem. A, 3, pp. 16198-16205 (2015)
[0112] (3) Aragón, M. J.; Lavela, P.; Alcántara, R.; Tirado, J. L. Effect of Aluminum Doping on Carbon Loaded Na3V2(PO4)3 as Cathode Material for Sodium-Ion Batteries. Electrochim. Acta, 2015, 180, 824–830. https: / / doi.org / 10.1016 / j.electacta.2015.09.044
[0113] (4) Liang, L.; Li, X.; Zhao, F.; Zhang, J.; Liu, Y.; Hou, L.; Yuan, C. Construction and Operating Mechanism of High-Rate Mo-Doped Na3V2(PO4)3@C Nanowires toward Practicable Wide-Temperature-Tolerance Na-Ion and Hybrid Li / Na-Ion Batteries. Adv. Energy Mater. 2021, 11(21), 1–17. https: / / doi.org / 10.1002 / aenm.202100287 .
[0114] (5) Liu, X.; Feng, G.; Wang, E.; Chen, H.; Wu, Z.; Xiang, W.; Zhong, Y.; Chen, Y.; Guo, X.; Zhong, B. Insight into Preparation of Fe-Doped Na3V2(PO4)3@C from Aspectsof Particle Morphology Design, Crystal Structure Modulation, and CarbonGraphitization Regulation. ACS Appl. Mater. Interfaces, 2019, 11, 12421–12430. https: / / doi.org / 10.1021 / acsami.8b21257 .
[0115] (6) Zakharkin, MV; Drozhzhin, OA; Ryazantsev, SV; Chernyshov, D.; Kirsanova, MA; Mikheev, IV; Pazhetnov, EM; Antipov, EV; Stevenson, KJ; Antipov, V.; Stevenson, KJElectrochemical Properties and Evolution of the Phase Transformation Behavior in the NASICON-Type Na 3+x Mn x V 2-x (PO4)3(0≤x≤1)Cathodes for Na-Ion Batteries[NASICON type Na 3+x Mn x V 2-x Evolution of electrochemical properties and phase transition behavior of (PO4)3 (0≤x≤1) cathode]. J. Power Sources, 2020, 470 (February), 228-231. https: / / doi.org / 10.1016 / j.jpowsour.2020.228231 .
[0116] Example 2: In situ monitoring of the formation of a material having formula (I)
[0117] The reaction between Na3V2(PO4)3 and Na1V2(PO4)3 in Example 1.1 was monitored by an in-situ temperature-controlled synchrotron radiation XRD pattern, as shown in FIG. Figure 1 As shown. Using a 0.5 mm diameter capillary, Data were collected in Debye-Scherrer geometry at a wavelength of . XRD patterns were collected every 3°C while a mixture of Na3V2(PO4)3 and Na1V2(PO4)3 in a 1:1 molar ratio was heated to 500°C and then cooled to 35°C. During heating, all XRD reflection peaks of the two phases Na3V2(PO4)3 and Na1V2(PO4)3 shifted to lower angles due to the main thermal expansion. As the temperature increased above about 300°C, the two phases began to disappear, Accompanied by the formation of a new single phase , and reaction 1 is completely completed at 500° C. During cooling, the XRD reflection peaks of the new single-phase material are maintained down to 35° C. without phase separation, with a slight peak shift to higher angles due to thermal contraction.
[0118] Example 3: Structural Characterization of Materials Having Formula (I)
[0119] Using the method described in Example 1.1, several materials of formula (I) with different compositions were prepared and compared with the two end members Na3V2(PO4)3 and Na1V2(PO4)3, as shown in Figure 2 Laboratory X-ray diffraction was performed on a PANalytical X'PertPro diffractometer in Co Kα1,2 The XRD patterns of the two phases with different ratios of Na3V2(PO4)3 and Na1V2(PO4)3 were used in reflection geometry under irradiation. Before heat treatment, two mixed phases with different ratios of Na3V2(PO4)3 and Na1V2(PO4)3 appeared in the XRD pattern. The XRD reflection peaks of the various compositions did not shift, but the intensities were relative to Figure 2 a. However, after heat treatment, the two mixed phases become a single phase. In addition, when Na x As x increases from 1 to 3 in V2(PO4)3, the reflection peak shifts to a lower angle.
[0120] This is done by using Figure 3 The structural analysis of the full pattern matching shown further confirmed that when in Na x Na in V2(PO4)3 + As the number of increases from 1 to 3, the unit cell volume per formula unit (V / Z) gradually increases, while the c / a ratio tends to decrease. For comparison purposes, the V / Z and c / a ratios of conventional Na3V2(PO4)3, Na2V2(PO4)3, and NaV2(PO4)3 are also shown.
[0121] Example 4: Comparison of the structure of the material having formula (I) according to the present invention and the electrochemically observed material Na2V2(PO4)3
[0122] For electrochemical observation of the material Na2V2(PO4)3, an in situ button cell with a glass window was used with Debye-Scherrer geometry. Operational synchrotron XRD measurements were performed. Synchrotron XRD patterns were collected every 30 min using a MYTHEN detector with a 2θ step size of 0.006° over a 2θ angle range of 2-40° with a collection time of 3.5 min. The working electrode consisted of Na3V2(PO4)3 powder and carbon black (80 / 20 weight ratio), and Na metal was used as the counter / reference electrode. The assembled button cells were heated at 2.0-4.3 V vs. Na + / Na in the voltage window at 0.77C (1C = 58.2mA / g, or 1Na + / 1e – Exchange about 9h).
[0123] Figure 4 A comparison of XRD patterns between a material of formula (I) according to the invention wherein x=2 (collected with a capillary) and electrochemically observed Na2V2(PO4)3 collected with an in situ cell during cycling according to the above procedure is shown. The difference in the Bragg peaks at clearly shows that the two structures are different.
[0124] Figure 5 Schematic diagram of the crystal structure of the material with formula (I) according to the present invention (left) and electrochemically observed Na2V2(PO4)3 (right) wherein x = 2. The obvious difference between the two structures is that the Na sites (sites where Na can be embedded and de-embedded) do not have the same position and do not have the same occupancy factor.
[0125] In the table below, the main parameters determined by structural analysis using the Rietveld method for the material according to the invention having formula (I) with x=2 and electrochemically observed Na2V2(PO4)3 are collected.
[0126]
[0127] Example 5: Electrochemical evaluation of materials having formula (I)
[0128] The electrochemical properties of the material of formula (I) in which x=2 were tested in a half-cell configuration in a CR2032 type button cell. The positive electrode consisted of an active material of formula (I) in which x=2, carbon black and poly(vinylidene fluoride) in a weight ratio of 73 / 18 / 9. Prior to cell assembly, the electrodes were dried at 80°C under vacuum for at least 12 hours. For the cell assembly, a piece of Waterman glass fiber (GF / D) was used as a separator, and the electrolyte consisted of 1M NaPF6 in ethylene carbonate (EC) / dimethyl carbonate (DMC) (1:1, w / w) (with 2 wt.% fluoroethylene carbonate (FEC)). The assembled button cells were charged at 2.5-4.3 V relative to Na + / Na cycled at 0.1C in the voltage window.
[0129] like Figure 6 As shown, the first charge and discharge capacities are 109.3 and 104.4 mAh / g, respectively, and the irreversibility is 4.5%. The voltage curves of the following cycles are very similar to those of the first cycle, indicating that the Na in Na2V2(PO4)3 according to the present invention + Extraction / embedding is highly reversible.
[0130] Example 6: In Na + Structural evolution of the material having formula (I) during extraction / intercalation
[0131] Using an in-situ cell with a Be window and equipped with Cu Kα1,2 Operational X-ray diffraction measurements were performed on a PANalyticalEmpyrean diffractometer using irradiation. XRD patterns were collected every hour at a 2θ step size of 0.0167° in a 2θ angle range of 12-40°. The working electrode consists of Na2V2(PO4)3 powder and carbon black (80 / 20, in wt%) with formula (I), and Na metal was used as a counter / reference electrode. The same diaphragm and electrolyte as those tested in button cells were used in the operational experiments of Example 5. Two different voltage regions were explored: 2.5-4.4V and 1.3-3.0V relative to Na + / Na, at 0.1C (1Na + / 1e – The XRD data were analyzed by the Rietveld method using FullprofSuite.
[0132] like Figure 7 As shown, during the cycle, the 2.5V-4.4V and 1.3V-3.0V relative to Na + The XRD reflection peaks in the two voltage windows of / Na are constantly shifted, confirming the solid solution mechanism. The evolution of the peak shift during charge and discharge is symmetrical, indicating that Na+ The extraction / intercalation mechanism remains unchanged. Moreover, the XRD pattern of Na2V2(PO4)3 obtained after the first cycle appears to be similar to the initial one, implying that the entire electrochemical reaction is highly reversible.
[0133] When at 2.5-4.4V relative to Na + When cycling between Na / Na, the Rietveld refinement results from the in-operation XRD measurements further confirmed that the electrochemical reactions during charge and discharge are symmetrical and reversible, as shown in Figure 2. Figure 8 The original material with formula (I) and the unit cell volume at the end of charging are respectively and The volume change is about 5.7%. When the electrochemical reaction involves a similar amount of Na + This is lower than the volume change of conventional Na3V2(PO4)3 (about 8.2%). The ratio of the c and a parameters increases until about mid-charge (about scan number 12) and then decreases until the end of charge.
[0134] About Na + Occupancy, Na in the structure + The total number of Na decreases gradually during charging and increases during discharging. + The main reason for the decrease in the number of Na(2) sites until the middle of the charge is the decrease in the occupancy factor of the Na(2) sites. Thereafter, the occupancy of the Na(1) sites decreases rapidly until the end of the charge, resulting in a decrease in the total Na(2) sites. + Further reduction (for the location of the Na1 and Na2 sites in the crystal structure of the material according to the invention, see Figure 5 ).
[0135] Example 7 (Comparative): Electrochemical and structural evaluation of conventional Na3V2(PO4)3
[0136] As a comparative example, conventional Na3V2(PO4)3 electrodes were used to Kα1,2 Operational X-ray diffraction measurements under irradiation at 2.5 and 4.3 V vs. Na + / Na between 0.1C (= 1 Na in 10h + ) is cycled at the same C-rate of the conventional Na3V2(PO4)3. + The insertion / extraction mechanism is different and shows the typical characteristics of a two-phase reaction between Na3V2(PO4)3 and Na1V2(PO4)3: during charging, the Na3V2(PO4)3 phase decreases while Na1V2(PO4)3 appears, and during discharge, the phase appearance / disappearance occurs in the opposite way. This phenomenon is Fig. 9 It can be seen that unlike the material having formula (I) of the present invention, the diffraction peaks corresponding to (104), (110) and (113) reflections from the two end members Na1V2(PO4)3 and Na3V2(PO4)3 clearly indicate a two-phase mechanism.
[0137] The battery volumes of Na3V2(PO4)3 and Na1V2(PO4)3 are and And the volume change was about 8.2%, as summarized in the table below.
[0138]
Claims
1. A material having formula (I): A x V (2-y-z) M y M’ z (PO4)3(I) in: A is Na or Li or a mixture of Na and Li, 1<x<3, 0≤y≤1, 0≤z≤1 M is an electroactive transition element or a mixture of at least two electroactive transition elements, M' is an electro-inactive element or a mixture of at least two electro-inactive elements, and The material having formula (I) exhibits to Changing V / Z ratio, The condition is that if x=2, then the V / Z ratio changes from to change.
2. The material according to claim 1, wherein A = Li and the V / Z ratio is from to change.
3. The material according to claim 1, wherein A = Na and the V / Z ratio is from to change.
4. The material of claim 3, wherein if x=2, the V / Z ratio is to 5. The material according to claim 3 or 4, wherein x varies from 1.5 to 2.
5.
6. The material according to any one of claims 3 to 5, wherein The V / Z ratio is to change.
7. A material according to any one of claims 3 to 6, described by a hexagonal unit cell and exhibiting lattice parameters a and c, wherein The c / a ratio varied from 2.510 to 2.
545.
8. The material according to any one of claims 3 to 7, described using a rhombohedral (R-3c) crystal structure having two sodium sites, Na(1) and Na(2), the average filling fraction of the Na(1) site being from 0.2 to 0.95 on the unit cell, and the average filling fraction of the Na(2) site being from 0 to 0.9 on the unit cell.
9. A material according to any preceding claim which is a single phase material.
10. A method for preparing a material having formula (I) according to any one of claims 1 to 9, comprising the following steps: a) Mixed A3V (2-α) Z α (PO4)3 and A1V (2-β) Z' β (PO4)3, preferably under an inert atmosphere, to obtain an initial mixture, wherein A=Li or Na or a mixture of Na and Li, Z and Z' are metal elements independently selected from electroactive transition elements, electroactive inactive elements and mixtures thereof, and 0≤α<1 and 0≤β<1, b) heating the initial mixture at a temperature between 300° C. and 700° C., preferably under an inert atmosphere or under vacuum.
11. The method according to claim 10, wherein: In the initial mixture, Na3V (2-w) M' w The mole fraction of (PO4)3 is p and Na1V (2-z) M” z The mole fraction of (PO4)3 is (1-p), where 0 <p<1。 12. A method for preparing a material having formula (I) according to any one of claims 1 to 9, comprising the following steps: 1) A3V (2-y-z) M y M' z (PO4)3 is dispersed in a solvent, preferably an organic solvent, wherein A is Na or Li or a mixture of Na and Li, 0≤y<1, 0≤z<1, M is an electroactive transition element or a mixture of at least two electroactive transition elements, M' is an electro-inactive element or a mixture of at least two electro-inactive elements, 2) Add oxidant to A3V (2-y-z) M y M' z In the dispersion of (PO4)3, 3) stirring the resulting mixture, and 4) Get an A x V (2-y-z) M y M' z (PO4)3, of which 1 <x<3。 13. Use of a material of formula (I) as defined in any one of claims 1 to 9 as an electrode active material for a battery, preferably as a positive electrode active material for a Li-ion or Na-ion battery, more preferably a Na-ion battery.
14. An electrode for a battery, preferably for a Li-ion or Na-ion battery, more preferably for a Na-ion battery, comprising at least one material of formula (I) as defined in any one of claims 1 to 9.
15. A battery, preferably a Li-ion or Na-ion battery, more preferably a Na-ion battery, comprising at least one material of formula (I) as defined in any one of claims 1 to 9 as an electrode active material, preferably as a positive electrode active material.
Citation Information
Cited By
Sodium ferric phosphate pyrophosphate composite positive electrode material for sodium ion battery and preparation method of sodium ferric phosphate pyrophosphate composite positive electrode material
CN121812540A